Perspectives of Nepalese Youth on Ecotourism Practiced at Rara National Park, Western Nepal - Aryal, Chandramani; Niroula, Narayan; Ghimire, Bina (Journal of Tourism & Adventure, 2019)
Participatory conservation approach practiced in most of the protected areas of Nepal mandate the active role of people for conservation planning and implementation. Peoples’ participation in conservation is largely regulated by the benefits they receive. Ecotourism, as it envisions the improved living standard of local people, could be one of the drivers for alluring local people towards biodiversity conservation. Thus, it is essential to assess ecotourism potential of a site for planning and implementing community engagement for biodiversity conservation. The potentiality of ecotourism depends upon three major factors i.e. visitors’ satisfaction, willingness of local people to participate in ecotourism related activities, and enthusiasm of park authority. Studies on ecotourism potential in Nepal are limited in scope and time. Therefore, this study tends to recognize the perspective of youth towards ecotourism in Rara National Park, where visitors’ numbers are growing of late. Scheduled interview was used to collect the perspectives of youth. Data were explored using descriptive statistics and association between the perceptions and visitors’ general background were explored using Chi-Square test. In the study, length of stay was observed to be associated with educational background. As per the responses, ecotourism activities in the park were found to contribute in biodiversity conservation and betterment of livelihood of local people. Though, the number of tourists are increasing, they are not adequate yet with potential to increase further in near future. When optimum tourist visit the park area, ecotourism activities can create win-win situation to biodiversity and people.